Clinical and nursing problems in Crohn’s disease - Wawrzycka, Iwona; Głuszek-Osuch, Martyna; Głuszek, Stanisław (Medical Studies/Studia Medyczne, 2013)
Introduction: Crohn’s disease (CD) is a transmural, typically granulomatous intestinal inflammation and may affect any part of the gastrointestinal tract, from the mouth to the anus. The complexity of the course of CD along with its complications (fistulas, perforation, and bleeding into the gastrointestinal tract) requires doctors and nurses to have specialised knowledge that conditions the treatment of this disease. Aim of the research : To present the clinical image and nursing problems of CD patients, based on the analysis of medical documentation of the Clinical Department of General, Oncological and Endocrine Surgery. Material and methods: The group under study was formed out of 34 patients with diagnosed CD, hospitalised within the years 2003–2011. The criteria for inclusion into the group were as follows: diagnosed CD, age of 18–80, male and female gender. The criteria for exclusion were connected with other inflammatory diseases of the intestines, the age being below 18, or admission due to another reason, e.g. a planned cholelithiasis surgery during a remission of CD. Results : Analysis of medical documentation concerned 34 patients with CD. There were 15 women (44.1%) and 19 men (55.9%) in the group; the minimal age was 20 and the maximal 77; the average age was 47.2 and the median 47. The minimum length of stay was 1 day, the maximum 32 days, the average 8.29, and the median 6.5. Analysis of the data showed that the duration of hospitalisation increases with age. There is no statistical interrelation between the length of stay at the hospital and the nature of the stay (emergency, planned). The duration of the disease was most often from 2 to 5 years in 12 cases (35.3%), in 7 cases (20.6%) this was 5 to 10 years, and in one person (2.9%) it was above 10 years. In 23.5% of patients, it was aches and pains that were the cause of going to hospital; other symptoms such as bleeding, diarrhoea and vomiting were a separate rarer cause of hospitalisation. During treatment the following complications were encountered: stroke – 1 (2.9%), endocarditis – 1 (2.9%), myocardial infarction – 1 patient (2.9%), shock – 1 (2.9%), deep surgical site infection – 1 (2.9%), and superficial surgical site infection – 2 (5.8%). Conclusions : In light of our own research, it may be stated that the most frequent causes of going to hospital in the case of CD patients are pain, nausea and vomiting as well as bleeding into the gastrointestinal tract. In the case of CD, for the examined patients, the most frequent locations were the final section of the small intestine and the initial part of the large intestine. The disease resulted, in a significant part of the patients, in the occurrence of complications such as fistulas, perforation and bleeding into the gastrointestinal tract. Such conditions are one of the most difficult clinical problems, for both doctors and nurses. Treatment of CD patients with complications requires doctors and nurses to have specialised knowledge of this disease and to treat its complications.